Evaluation of Exercise Tolerance in Non-obstructive Hypertrophic Cardiomyopathy With Myocardial Work and Peak Strain Dispersion by Speckle-Tracking Echocardiography - Su, Ye; Peng, Qionghui; Yin, Lixue; Li, Chunmei (Frontiers in Cardiovascular Medicine, 2022)
Background The aim of this study was to evaluate exercise tolerance in non-obstructive hypertrophic cardiomyopathy (HCM) by investigating the value of myocardial work (MW) combined with strain peak dispersion. Methods A total of 65 patients with non-obstructive HCM and normal left ventricular ejection fraction were enrolled and 60 healthy subjects were selected as controls. The automated function imaging (AFI)-two-dimensional ultrasonic speckle-tracking technology was used to obtain the values for peak global longitudinal strain (GLS), longitudinal strain peak time dispersion (PSD), 18-segment systolic longitudinal peak strain (LPS), 18-segment longitudinal strain peak time (TTPLS), global waste work (GWW), global constructive work (GCW), global work index (GWI), global work efficiency (GWE), and exercise metabolic equivalents (METS). Results (1) Values for LV-GLS (−17.77 ± 0.20 vs. −21.66 ± 0.42%) were lower and PSD (95.10 ± 8.15 vs. 28.97 ± 1.50 ms) was prolonged in patients with HCM (p < 0.01). (2) An increasing trend was shown in the basal segment < intermediate segment < apical segment for both patients with HCM and controls, although each segment had lower values in the HCM group. (3) TTPLS was prolonged in the HCM group (p < 0.01). (4) GWE, GWI, and GCW were all lower (p < 0.01) and GWW was higher in patients with HCM (p < 0.01). (5) Values of GWE were less than 92.5%, GWI less than 1,200 mmHg, GCW less than 1,399 mmHg, these abnormal values are helpful for the diagnosis of impaired exercise tolerance and poor prognosis (6) The METS and LV-GLS of HCM in the asymmetric group were significantly lower than that in AHCM group, but the PSD was significantly greater than that in the AHCM group. Values of LPS-BL (−13.13% ± 2.51% vs −10.17% ± 2.20%) in the apical HCM group were better than in the asymmetric HCM group (p < 0.05). Conclusion GCW, GWI, and GWE can be safely measured by resting echocardiography to evaluate exercise tolerance in patients with HCM who cannot perform an exercise-based examination. Such measurements provide a basis for clinical decisions regarding exercise and drug prescription.